The State of Research on the Manichaean Bishop Faustus - Gaans, Gijs M. van (HTS teologiese studies, 2013)
According to Augustine’s own Confessiones, the Manichaean bishop Faustus of Milevis played a significant role in his apostasy from Manichaeism. Somehow Augustine became disappointed with the intellectual explanations Faustus provided for some of Manichaeism’s fabulous doctrines and thereby with Manichaeism as a religion. That same Faustus published a work, the Capitula in which he discussed some exegetical controversies. This work has been preserved, because Augustine cited it in its entirety in his Contra Faustum Manichaeum. In the last hundred years Faustus and his work have received some significant scholarly attention. During that period our view of Manichaeism and subsequently on the Manichaean bishop, has changed. At the beginning Faustus’s exegesis was considered merely a form of Manichaean propaganda. Its Christian elements were accepted as a tactic tool in order to covert Catholic Christians to Manichaeism, which was not considered a Christian religion at all. In the course of the 20th century primary Manichaean sources have been discovered. They have enhanced our understanding of the ancient religion immensely. Comparing these texts with Faustus’s Capitula reveals that the Manichaean bishop not only defended well-known Manichaean dogmas through his exegesis of scripture, he seems to have contributed to Manichaean exegesis and even Manichaean prophetology. Furthermore, Faustus’s Christian, Pauline language can no longer be accepted as a mere tactic adaption to Catholic preferences, but seems to have been his own, genuine language. This article provides an overview of both the research and the debates on bishop Faustus and his works.